Decreased melanoma CSF-1 secretion by Cannabigerol treatment reprograms regulatory myeloid cells and reduces tumor progression - Iris Wyrobnik; Miryam Steinberg; Anat Gelfand; Ronen Rosenblum; Yara Eid Mutlak; Liron Sulimani; Shiri Procaccia; Yishai Ofran; Hila Novak-Kotzer; David Meiri (OncoImmunology)
During solid tumor progression, the tumor microenvironment (TME) evolves into a highly immunosuppressive milieu. Key players in the immunosuppressive environment are regulatory myeloid cells, including myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs), which are recruited and activated via tumor-secreted cytokines such as colony-stimulating factor 1 (CSF-1). Therefore, the depletion of tumor-secreted cytokines is a leading anticancer strategy. Here, we found that CSF-1 secretion by melanoma cells is decreased following treatment with Cannabis extracts. Cannabigerol (CBG) was identified as the bioactive cannabinoid responsible for the effects. Conditioned media from cells treated with pure CBG or the high-CBG extract reduced the expansion and macrophage transition of the monocytic-MDSC subpopulation. Treated MO-MDSCs also expressed lower levels of iNOS, leading to restored CD8+ T-cell activation. Tumor-bearing mice treated with CBG presented reduced tumor progression, lower TAM frequencies and reduced TAM/M1 ratio. A combination of CBG and αPD-L1 was more effective in reducing tumor progression, enhancing survival and increasing the infiltration of activated cytotoxic T-cells than each treatment separately. We show a novel mechanism for CBG in modulating the TME and enhancing immune checkpoint blockade therapy, underlining its promising therapeutic potential for the treatment of a variety of tumors with elevated CSF-1 expression.